2017
DOI: 10.1007/s10964-017-0790-5
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Pathways from Parental Socioeconomic Status to Adolescent Substance Use: Alternative and Complementary Reinforcement

Abstract: Although lower socioeconomic status has been linked to increased youth substance use, much less research has determined potential mechanisms explaining the association. The current longitudinal study tested whether alternative (i.e., pleasure gained from activities without any concurrent use of substances) and complementary (i.e., pleasure gained from activities in tandem with substance use) reinforcement mediate the link between lower socioeconomic status and youth substance use. Further, we tested whether al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 90 publications
3
34
1
Order By: Relevance
“…The impact of the family's SES on the health habits of adolescents is the subject of ongoing research by scientists and health policy makers, as they have a major impact on their future psychophysical development [1][2][3][4][5]. According to research, available in literature, adolescents living in low-SES families tend to be prone to risky and unhealthy behaviors, including the cigarettes, alcohol and marijuana use [3,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of the family's SES on the health habits of adolescents is the subject of ongoing research by scientists and health policy makers, as they have a major impact on their future psychophysical development [1][2][3][4][5]. According to research, available in literature, adolescents living in low-SES families tend to be prone to risky and unhealthy behaviors, including the cigarettes, alcohol and marijuana use [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…The attitude of the experts prevails that SES plays an important role in the development of adolescents, and therefore also on the adolescent's decision to start consuming some of the dangerous and illicited substances [13,14]. Contrary to those attitudes, there are allegations that the link between SES and the cigarettes, alcohol and illicit drugs use has not been fully clarified and that the family's SES and behavior of their members cannot be verified with certainty [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic status (SES) is one of several factors that influence substance use among individuals across the lifespan (Jones et al, 2016). Numerous studies have investigated the association between different SES indicators and the use of alcohol and other substances during adolescence and young adulthood (Humensky, 2010; Patrick et al, 2012; Finch et al, 2013; Kendler et al, 2014; Latvala et al, 2014; Lui et al, 2015; Pedersen et al, 2015; Charitonidi et al, 2016; Non et al, 2016; Gomes de Matos et al, 2017; Jang et al, 2017; Pape et al, 2017, 2018; Lee et al, 2018). The nature of this association is complex, and the link seems to be dependent on both how SES is measured and operationalized, the substance in question, the type of use, and the participating adolescents’ age (Ensminger et al, 2000; Boyce et al, 2006; Currie et al, 2008; Kendler et al, 2014; Charitonidi et al, 2016; Pape et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…With regards to the association between individual-level SES and substance use, all of the previously published studies are, to the best of our knowledge, based on self-reported or parental-reported SES (Humensky, 2010; Patrick et al, 2012; Finch et al, 2013; Kendler et al, 2014; Latvala et al, 2014; Lui et al, 2015; Charitonidi et al, 2016; Non et al, 2016; Gomes de Matos et al, 2017; Jang et al, 2017; Pape et al, 2017, 2018; Lee et al, 2018). The use of self-reported SES may be prone to bias and systematic missing data (Ensminger et al, 2000; Svedberg et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation